2021
DOI: 10.1073/pnas.2026245118
|View full text |Cite
|
Sign up to set email alerts
|

Physiological concentrations of cyanide stimulate mitochondrial Complex IV and enhance cellular bioenergetics

Abstract: In mammalian cells, cyanide is viewed as a cytotoxic agent, which exerts its effects through inhibition of mitochondrial Complex IV (Cytochrome C oxidase [CCOx]). However, the current report demonstrates that cyanide’s effect on CCOx is biphasic; low (nanomolar to low-micromolar) concentrations stimulate CCOx activity, while higher (high-micromolar) concentrations produce the “classic” inhibitory effect. Low concentrations of cyanide stimulated mitochondrial electron transport and elevated intracellular adenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 13 publications
(15 reference statements)
6
25
0
Order By: Relevance
“…Not unlike phenazines, which were also first categorized as “mere secondary metabolites” and which later turned out to act as internal signalling molecules with diverse and important cellular functions 28 , we show here that HCN is much more than a respiratory toxin, and acts as an inter- and extracellular signal on both producing and receiving cells. These findings are in line with recent reports on the ability of HCN to induce broad physiological effects in both plant and human cells 29,30 . Compared with phenazines, HCN is a volatile molecule and as such, its zone of influence is expected to be much broader 1 .…”
supporting
confidence: 93%
“…Not unlike phenazines, which were also first categorized as “mere secondary metabolites” and which later turned out to act as internal signalling molecules with diverse and important cellular functions 28 , we show here that HCN is much more than a respiratory toxin, and acts as an inter- and extracellular signal on both producing and receiving cells. These findings are in line with recent reports on the ability of HCN to induce broad physiological effects in both plant and human cells 29,30 . Compared with phenazines, HCN is a volatile molecule and as such, its zone of influence is expected to be much broader 1 .…”
supporting
confidence: 93%
“…Similarly, S‐glutathionylation, a post‐translational modification involved in modulation of energy metabolism and oxidative damage prevention, has been observed in different mitochondrial complexes, including CCOx [ 27 , 28 ]. As shown working on HepG2 cells and isolated enzyme from bovine heart, we have reported that S‐glutathionylation induces a downregulation of CCOx activity, and interestingly, this post‐translational modification could be reversed by nanomolar concentrations of cyanide [ 29 ]. As discussed below, CCOx is also targeted by NO which is responsible for partial inhibition of its enzymatic activity and maintaining ΔΨ m levels under control [ 30 ].…”
Section: Cyanide As An Inhibitor Of Mitochondrial Respiration and As ...mentioning
confidence: 99%
“…A subsequent study comparing the binding parameters of cyanide to different states of CCOx, estimated that the partially reduced enzyme, populated during turnover, displays a binding affinity to cyanide that is 5 orders of magnitude higher as compared to the fully oxidized enzyme [ 34 ]. As shown by sequential mixing and rapid scan stopped flow spectroscopy, a one‐electron reduction of a 3 /Cu B is sufficient to induce a rapid cyanide binding [ 29 ]. According to this model, the very first binding site is Cu B and two possible mechanisms are conceivable.…”
Section: Cyanide As An Inhibitor Of Mitochondrial Respiration and As ...mentioning
confidence: 99%
“…However, it was discovered that in mammals H 2 S has physiological relevance and is endogenously generated [ 1 , 2 ]. Currently, H 2 S is considered to be a member of the class of gasotransmitters or, in other words, endogenous gaseous signaling molecules, along with nitric oxide and carbon monoxide [ 3 , 4 , 5 , 6 , 7 ]. Although still debated, cyanide has also recently been proposed to be part of this class [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, H 2 S is considered to be a member of the class of gasotransmitters or, in other words, endogenous gaseous signaling molecules, along with nitric oxide and carbon monoxide [ 3 , 4 , 5 , 6 , 7 ]. Although still debated, cyanide has also recently been proposed to be part of this class [ 7 , 8 ]. H 2 S contributes to the regulation of important physiological processes in the cardiovascular, gastrointestinal, nervous, and respiratory systems.…”
Section: Introductionmentioning
confidence: 99%